PENGARUH GAJI, PROMOSI JABATAN, DAN REKAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. BANK RAKYAT INDONESIA (PERSERO) TBK, KANTOR CABANG BIREUEN - Simahatie, Mai; Iba, Zainuddin (indOmera, 2021)
The purpose of this study was to see 1) The effect of salary on job satisfaction of BRI employees in the Bireuen Branch, 2) the effect of promotion on job satisfaction of employees of the BRI Bireuen Branch, 3) The influence of colleagues on job satisfaction of employees of the BRI Bireuen Branch, 4) The effect of salary, promotion position, colleagues on job satisfaction of BRI employees at the Bireuen Branch jointly (simultaneously). This research was conducted at PT Bank Rakyat Indonesia (Persero) Tbk Bireuen Branch Office, having its address at Jl Medan Banda Aceh Simpang 4 Bireuen. As for the variables in this study are salary, promotion, coworkers, and job satisfaction. The population in this study were all employees of BRI Bireuen Branch as many as 182 employees. Determination of the sample using the Slovin formula and the results are 125 people. The research method used is quantitative research. The analysis used is multiple regression analysis with the help of SPSS 17 and shows the results: from three independent variables, namely salary, job promotion and co-workers, it is found that salaries and co-workers partially affect employee job satisfaction with the value of the salary regression coefficient (X1). is 0.288 and co-workers (X3) is 0.451 while Job Promotion (X2) has no effect with the regression coefficient value of 0.63. Simultaneously, salary, job promotion, coworkers have an effect on job satisfaction of employees of BRI Bireuen Branch, the value of R Squer is 0.754 or 75.4%, the rest is influenced by other factors that are not discussed